2011
DOI: 10.5860/crl-167
|View full text |Cite
|
Sign up to set email alerts
|

Almost Halfway There: An Analysis of the Open Access Behaviors of Academic Librarians

Abstract: Academic librarians are increasingly expected to advocate for scholarly communications reforms such as open access to scholarly publications, yet librarians do not always practice what they preach. Previous research examined librarian attitudes toward open access, whereas this article presents results of a study of open access publishing and self-archiving behaviors of academic librarians. Following an analysis of open access to library and information science literature in 2008, several strategies to encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…A mashup of the two datasets can be seen in Figure 9, where the bars represent the occurrence of a barrier as a topic in the LIS literature (LIS interest) and the stars denote Björk's ranking system (three=high). This comparison shows similarities, for example in in 2004 4 the academic reward system, business models, and marketing are assigned the highest rank by Björk and concurrently show the highest percentage of articles (interest) for that year. It certainly stands to reason that if a topic is considered disruptive to an existing system, the professionals in the field would be discussing the topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mashup of the two datasets can be seen in Figure 9, where the bars represent the occurrence of a barrier as a topic in the LIS literature (LIS interest) and the stars denote Björk's ranking system (three=high). This comparison shows similarities, for example in in 2004 4 the academic reward system, business models, and marketing are assigned the highest rank by Björk and concurrently show the highest percentage of articles (interest) for that year. It certainly stands to reason that if a topic is considered disruptive to an existing system, the professionals in the field would be discussing the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries and information professionals have always been involved in supporting access to information and knowledge and they play a vital and active role in the success of the open access movement [4,5]. One way to gain an understanding of the discourse around open access is to study the views of the library and information science (LIS) community.…”
Section: Open Accessmentioning
confidence: 99%
“…Based on a study analyzing academic librarians' peer-reviewed articles published in LIS journals in 2008, Mercer (2011) found that academic librarians were slightly more likely to self-archive articles than others publishing in LIS journals, although many more articles were eligible for self-archiving than were made openly available. Palmer, Dill, and Christie's (2009) national study of librarians found support for and professional connections to OA while surfacing dissonance between this support and librarian publishing patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LIS scholars and practitioners have been at the forefront of promoting OA, but previous studies show that the adoption of OA as a method of publication in LIS-related academic works (and research in general) has not been as high as expected (Bowley and Vandegrift 2014, Mercer 2011, Way 2010, Xia, Wilhoite & Myers 2011. The majority of studies investigated the general adoption of OA by LIS scholars and practitioners.…”
Section: Introduction and Background Informationmentioning
confidence: 99%